2020
DOI: 10.1007/s00701-020-04495-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of the subthalamic nucleus in Parkinson’s disease: the effect of fiber tract stimulation on tremor control

Abstract: Background Therapeutic effects of deep brain stimulation (DBS) of the subthalamic nucleus (STN) in Parkinson’s disease (PD) may in parts be attributed to the stimulation of white matter near the targeted structure. The dentato-rubro-thalamic (DRT) tract supposed to improve tremor control in patients with essential tremor could be one candidate structure. The aim of this study was to investigate the effect of stimulation proximity to the DRT on tremor control in PD patients treated with STN-DBS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Symptom‐specific sweet‐spot analysis of the model showed optimal suppression of akinetic‐rigid symptoms again in the dorsolateral region of the STN, whereas tremor suppression was greatest in the zona incerta close to the ventral intermediate nucleus of the thalamus. These findings are in line with accumulating evidence, suggesting that the dentato‐rubro‐thalamic tract might be a common target structure for tremor suppression across multiple underlying pathologies 2,49‐52 . However, in the case of parkinsonian tremor, stimulating the STN proper might bear therapeutic effects as well 53 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Symptom‐specific sweet‐spot analysis of the model showed optimal suppression of akinetic‐rigid symptoms again in the dorsolateral region of the STN, whereas tremor suppression was greatest in the zona incerta close to the ventral intermediate nucleus of the thalamus. These findings are in line with accumulating evidence, suggesting that the dentato‐rubro‐thalamic tract might be a common target structure for tremor suppression across multiple underlying pathologies 2,49‐52 . However, in the case of parkinsonian tremor, stimulating the STN proper might bear therapeutic effects as well 53 .…”
Section: Discussionsupporting
confidence: 87%
“…These findings are in line with accumulating evidence, suggesting that the dentato-rubro-thalamic tract might be a common target structure for tremor suppression across multiple underlying pathologies. 2,[49][50][51][52] However, in the case of parkinsonian tremor, stimulating the STN proper might bear therapeutic effects as well. 53 Nonetheless, the symptom specificity related to different anatomical target structures indicates that individual symptomatology could influence the optimal contact selection.…”
Section: Model Validation and Anatomical Implicationsmentioning
confidence: 99%
“…Of the 60 identified studies, 39 studies focused on patients with Parkinson’s disease, 23‐61 10 studies focused on patients with dystonia syndromes, 62‐71 and 11 studies focused on patients with essential tremor (and additional tremor subtypes). 72‐82 Information regarding authors, study sample sizes (n), movement disorder diagnosis, targeted DBS region, main structural MRI technique utilized (MRI), clinical scale, post-operative follow-up period(s) and summarized main findings are presented as supplementary material (see Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Abdulbaki et al . [ 1 ] observed that better tremor control in PD patients correlated with the distance of active electrode contacts to the DRT and suggested that tractography may optimize DBS targeting and postoperative adjustment of stimulation parameters.…”
Section: Discussionmentioning
confidence: 99%